FN1–EGF gene fusions are recurrent in calcifying aponeurotic fibroma. Issue 4 (March 2016) - Puls, Florian; Hofvander, Jakob; Magnusson, Linda; Nilsson, Jenny; Haywood, Elaine; Sumathi, Vaiyapuri P; Mangham, D Chas; Kindblom, Lars‐Gunnar; Mertens, Fredrik
Abstract: Calcifying aponeurotic fibroma (CAF) is a soft tissue neoplasm with a predilection for the hands and feet in children and adolescents. Its molecular basis is unknown. We used chromosome banding analysis, fluorescence in situ hybridization (FISH), mRNA sequencing (RNA‐seq), RT‐PCR, and immunohistochemistry to characterize a series of CAFs. An insertion ins(2;4)(q35;q25q?) was identified in the index case. Fusion of the FN1 and EGF genes, mapping to the breakpoint regions on chromosomes 2 and 4, respectively, was detected by RNA‐seq and confirmed by RT‐PCR in the index case and two additional cases. FISH on five additional tumours identified FN1–EGF fusions in all cases. CAFs analysed by RT‐PCR showed that FN1 exon 23, 27 or 42 was fused to EGF exon 17 or 19. High‐level expression of the entire FN1 gene in CAF suggests that strong FN1 promoter activity drives inappropriate expression of the biologically active portion of EGF, which was detected immunohistochemically in 8/9 cases. The FN1–EGF fusion, which has not been observed in any other neoplasm, appears to be the main driver mutation in CAF. Although further functional studies are required to understand the exact pathogenesis of CAF, the composition of the chimera suggests an autocrine/paracrine mechanism of transformation. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.